AB0573 The Disease Associations of Takayasu's Arteritis. (15th July 2016) - Esatoglu, S.N.; Celik, A.M.; Ucar, D.; Celik, A.F.; Ugurlu, S.; Hatemi, G.; Melikoglu, M.; Fresko, I.; Hamuryudan, V.; Ozdogan, H.; Yurdakul, S.; Yazici, H.; et al.
Abstract : Background: Case reports or small case series suggest that Takayasu arteritis (TA) can co-exist with various chronic inflammatory disorders. Inflammatory bowel disease [(IBD; Crohn's disease (CD) or ulcerative colitis (UC)] has been the most common association. Objectives: We conducted a formal study to look specifically at the frequency of association of such chronic inflammatory disorders in a large cohort of patients with TA followed at a single tertiary center. Methods: There were 226 (200 F/26 M) patients registered with a diagnosis of TA at the Rheumatology Department of Cerrahpasa Medical Faculty, between 1977 and December 2015. Of these, 17 (8%) had died and 15 (7%) were lost to follow-up. The remaining 194 patients were called back at the outpatient clinic for an interview and for a physical examination. A standardized form sought whether the patient was also diagnosed as IBD, ankylosing spondylitis (AS), Behçet's syndrome (BS), amyloidosis (AA), uveitis, rheumatoid arthritis (RA), systemic lupus erythematosus, systemic sclerosis, Sjögren syndrome, psoriatic arthritis, myositis, small vessel vasculitis, a demyelinating or any other autoimmune or inflammatory disorder. The presence of skin-mucosa lesions ascribed to BS and inflammatory back pain were also specifically sought for. In addition to the self-reported information, patient charts and all medical documentation available such as hospitalization reports, imaging studies and blood work were used as a source of information. Results: One hundred and fifty-three (136 F/17 M) patients were studied. The mean age at the onset of symptoms was 31±11 years and at the time of TA diagnosis was 34±12 years. Subclavian artery was the most common involved artery (83%), followed by common carotids (75%) and aorta (64%). Currently, while 25 (16%) patients were off treatment, 72 (47%) patients were using glucocorticoids, 47 (31%) azathioprine, 32 (21%) methotrexate and 44 (29%) biological agents. We identified 11 (7%) patients with IBD (CH/UC:7/4), 11 (7%) with AS, and 9 (6%) with BS. Ten patients (6 IBD and 4 BS) were diagnosed simultaneously. The onset of TA preceded AS in 6 patients, IBD in 2, and BS in 1 as shown in Table . Among the remaining 122 patients, when the 31 patients with IBD, AS and BS were excluded, recurrent oral ulcers were present in 19 (16%), erythema nodosum in 13 (11%), arthritis in 12 (10%), papulopustular lesions in 5 (4%), uveitis in 5 (4%), and genital ulcer in 1. Inflammatory back pain was reported by 44 (36%) patients; this was usually in the dorsal spine level alone (n=30), less commonly in both dorsal and lumbar spine (n=10) and in the lumbar spine alone (n=4). In addition, 3 patients had secondary amyloidosis, 1 had RA and 1 morphea. We also observed 2 patients with autoimmune hepatitis and 2 with psoriasis, all having onset after anti-TNF treatment. Conclusions: This survey shows that TA co-occur with IBD, AS or BS in about 1/5 of the patients, at least in a hospital setting and this seems to be without a clear temporal pattern. The rather high prevalence of inflammatory back pain in the dorsal spine in TA needs further scrutiny. Disclosure of Interest: None declared